Health-related quality of life after camp-based family obesity treatment: an RCT. Issue 1 (3rd April 2019) - Benestad, Beate; Karlsen, Tor-Ivar; Småstuen, Milada Cvancarova; Lekhal, Samira; Hertel, Jens Kristoffer; Steinsbekk, Silje; Kolotkin, Ronette L; Ødegård, Rønnaug Astri; Hjelmesæth, Jøran
Abstract : Objective: To compare the effects of a 2-year camp-based immersion family treatment for obesity with an outpatient family-based treatment for obesity on health-related quality of life (HRQoL) in two generations. Design: Randomised controlled trial. Setting: Rehabilitation clinic, tertiary care hospital and primary care. Patients: Families with at least one child (7–12 years) and one parent, both with obesity. Interventions: Summer camp for 2 weeks, with four repetition weekends, or lifestyle school, including four outpatient days over 4 weeks. Behavioural techniques to promote a healthier lifestyle. Main outcome measures: Children's and parents' HRQoL were assessed using generic and obesity-specific measures. Outcomes were analysed using linear mixed models according to intention to treat, and multiple imputations were used for missing data. Results: Ninety children (50% girls) with a mean (SD) age of 9.7 (1.2) years and body mass index 28.7 (3.9) kg/m 2 were included in the analyses. Summer camp children had an estimated mean (95% CI) of 5.3 (0.4 to 10.1) points greater improvement in adiposity-specific HRQoL score at 2 years compared with the lifestyle school children, and this improvement was even larger in the parent proxy-report, where mean difference was 7.3 (95% CI 2.3 to 12.2). Corresponding effect sizes were 0.33 and 0.44. Generic HRQoL questionnaires revealed no significant differences between treatment groups in either children or parents from baseline to 2 years. Conclusions: A 2-year family camp-based immersion obesity treatment programme had significantly larger effects on obesity-specific HRQoL in children's self-report and parent proxy-reports in children with obesity compared with an outpatient family-based treatment programme. Trial registration number: NCT01110096 .